The cholinergic system, intelligence, and dental fluorosis in school-aged children with low-to-moderate fluoride exposure - Sumei Wang (Elsevier, 2021)
Disruption of cholinergic neurotransmission can affect cognition, but little is known about whether low-to-moderate fluoride exposure affects cholinergic system and its effect on the prevalence of dental fluorosis (DF) and intelligence quotient (IQ). A cross-sectional study was conducted to explore the associations of moderate fluoride exposure and cholinergic system in relation to children's DF and IQ. We recruited 709 resident children in Tianjin, China. Ion selective electrode method was used to detect fluoride concentrations in water and urine. Cholinergic system was assessed by the detection of choline acetyltransferase (ChAT), acetylcholinesterase (AChE) and acetylcholine (ACh) levels in serum. Compared with children in the first quartile, those in fourth quartile the risk of either developing DF or IQ < 120 increased by 19% and 20% for water and urinary fluoride. The risk of having both increased by 58% and 62% in third and fourth quartile for water fluoride, 52% and 65% for urinary fluoride. Water fluoride concentrations were positively associated with AChE and negatively associated with ChAT and ACh, trends were same for urinary fluoride except for ACh. The risk of either developing DF or having non-high intelligence rose by 22% (95%CI: 1.07%, 1.38%) for the fourth quartile than those in the first quartile of AChE, for having the both, the risk was 1.27 (95%CI: 1.07, 1.50), 1.37 (95%CI: 1.17, 1.62) and 1.44 (95%CI: 1.23, 1.68) in second, third and fourth quartiles. The mediation proportion by AChE between water fluoride and either developing DF or IQ < 120 was 15.7%. For both to exist, the proportion was 6.7% and 7.2% for water and urinary fluoride. Our findings suggest low-to-moderate fluoride exposure was associated with dysfunction of cholinergic system for children. AChE may partly mediate the prevalence of DF and lower probability of having superior and above intelligence.